Assessing technical efficiency of vegetable farms in North Macedonia - Martinovska Stojcheska, Aleksandra; Janeska Stamenkovska, Ivana; Kotevska, Ana; Dimitrievski, Dragi; Žgajnar, Jaka (Journal of Central European Agriculture, 2021)
Farm economic performance measuring is important for farm management purposes and for assessing the impact of agricultural policy measures. Efficiency studies enable assessment of farm performance since highly efficient farms are considered to have higher potential for operating in a changing economic and technological environment. The aim of this paper is to assess the technical efficiency of vegetable farms in North Macedonia, utilising Data Envelopment Analysis, as a non-parametric approach estimating the relative efficiency of decision making units producing multiple outputs and using multiple inputs. The analysis is based on Farm Monitoring System data including 75 vegetable farms in 2011 survey. Apart from baseline scenario, additional scenarios include available agricultural policy support in 2011 and 2016. The average technical efficiency of vegetable farms is 0.62 considering constant returns to scale, i.e. 0.71 and 0.75 considering variable returns to scale (in output and input oriented perspective, respectively). With better farm management, technical efficiency score can be improved on average by 25%. Technical efficiency increases slightly with subsidies, on average by 2 to 3%. Analyses based on farm level data, are valuable when estimating the effects of implementation of agricultural policy as well as when creating new policy interventions.